Implementation of Religious Moderation in the Subdistrict of Pulo Brayan (Analytical Study of Religious Moderation in Surah al-Kâfirun) - Nazil Mumtaz Al Mujtahid; Rifqi Ikhsanul Akmal; Muhammad Hidayatullah; Adira Hamdi (Pena Cendekia Insani, 2021)
Because Indonesia is a pluralistic society, religious moderation has an impact on society. Because moderation means reducing extremism, religious moderation is a program to reduce the number of community fanaticism and extremism in religion. Essentially, religious moderation serves a good purpose, but in practice, people have been unable to love one another and set aside religious fanaticism.